From synonym to valid species: Redescriptions of Ampharete acutifrons (Grube, 1860) and A. cirrata Webster & Benedict, 1887, and brief descriptions of A. baltica Eliason, 1955 and A. grubei Malmgren, 1865 (Annelida: Terebellida: Ampharetidae) - Krüger, Lotte; Dietrich, Anna; Bastrop, Ralf; Bick, Andreas (Zootaxa, 2022)
This paper aims mainly to provide clarity on the morphological characters of the type species of Ampharete, Ampharete acutifrons (Grube, 1860). Its common occurrence and wide distribution are most likely a result of misidentification of different species. Possible reasons for that are the brief original description of this species that is available solely in Latin and a series of questionable synonymizations, resulting in a confusing history of A. acutifrons. In addition to a detailed redescription of the holotype of A. acutifrons, we describe an Ampharete species from the Baltic Sea that has also been incorrectly identified as A. acutifrons for many decades. The individuals of this species agree in all diagnostic characters with those of the Northwest Atlantic species Ampharete cirrata Webster & Benedict, 1887. Since no differences were found, but it is clearly distinct from A. acutifrons, A. cirrata is recognised as a valid species and consequently deleted from the synonym list of A. acutifrons. We additionally examined type material of A. grubei Malmgren, 1865 and those of A. grubei baltica Eliason, 1955, now accepted as A. baltica. According to this, both species are valid, and A. grubei must therefore also be deleted from the list of synonyms of A. acutifrons. Information on five molecular markers (Histone H3, COI, 16S, 18S, 28S) is provided for A. cirrata from the Baltic Sea. DNA sequences (H3, 16S, 28S) were identical to sequences of a specimen found in Iceland that was incorrectly determined as A. acutifrons, supporting the assumption of an amphiatlantic distribution of A. cirrata. By comparing obtained sequences to available sequences in GenBank and BOLD, we found evidence that at least four species were previously misidentified as A. acutifrons. The historical course of the taxonomy of A. acutifrons demonstrates the importance of carefully studying type material and type locality material, respectively. We believe that most previous records and synonyms of A. acutifrons have been identified incorrectly and should be re-evaluated. Additionally, an updated key to all species of Ampharete from the North Atlantic is provided.